2019
DOI: 10.3390/ijerph17010182
|View full text |Cite
|
Sign up to set email alerts
|

Community Determinants of Physical Growth and Cognitive Development among Indian Children in Early Childhood: A Multivariate Multilevel Analysis

Abstract: Inadequate child physical growth and cognitive development share common individual-level risk factors. Less understood is how outcomes co-cluster at the community level and to what extent certain community-level characteristics influence the clustering. This study aims to quantify the extent to which child growth and development co-occur across communities, and to identify community-level characteristics associated with the clustering of the two development dimensions. We used longitudinal data from 1824 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The exact relationship between growth and ECD has not been well established as both are affected by common factors such as diet, childcare, community, and infectious diseases, indicating that their association may be a co-occurrence, causal, or a combination, i.e., both causal and co-occurrence [ 6 , 7 ]. Despite this ambiguity, several studies have shown that ECD and child’s physical growth are interconnected [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The exact relationship between growth and ECD has not been well established as both are affected by common factors such as diet, childcare, community, and infectious diseases, indicating that their association may be a co-occurrence, causal, or a combination, i.e., both causal and co-occurrence [ 6 , 7 ]. Despite this ambiguity, several studies have shown that ECD and child’s physical growth are interconnected [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physical growth, in terms of weight, height and body mass index (BMI), is considered a parameter that reflects the pattern of growth and development in a community. 1,2 Weight-for-age, height-for-age and BMI-for-age percentiles provide essential information to infer the nutritional and health status of children and adolescents. [3][4][5] The real value of growth curves for weight, height and BMI is that they help determine the degree to which the physiological needs of children and adolescents are being met during their growth and motor development process, 6 that is, anthropometric measurement is an early method and a suitable data source for assessing growth in this population.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, human growth has been widely studied due to its association with the socio economic status [1]. Especially, the study of physical growth in children or infants is an interesting and challenging and which depends on many factors such as genetic, malnutrition, physiological and socio-economic factors [2][3][4]. Normal growth is the greatest indicator of children's well-being and provides an accurate marker of inequalities in human development.…”
Section: Introductionmentioning
confidence: 99%